Meticillin‐resistant Staphylococcus aureus colonisation and infection in Thoroughbred racehorses and veterinarians in Japan. (7th May 2016) - Kuroda, T.; Kinoshita, Y.; Niwa, H.; Shinzaki, Y.; Tamura, N.; Hobo, S.; Kuwano, A.
Abstract : Meticillin‐resistant Staphylococcus aureus (MRSA) infections have been confirmed in hospitalised Thoroughbred racehorses at the hospitals of two training centres in Japan since 2009. To investigate the source of infection, the authors examined the rate of nasal MRSA colonisation in 600 healthy Thoroughbred racehorses, 53 veterinarians and 16 office staff at the racehorse hospitals of the two training centres. MRSA was not isolated from healthy Thoroughbred racehorses or hospital office staff. However, MRSA was isolated from 16 veterinarians (30.1 per cent), and the colonisation rate was significantly higher in veterinarians than in the office staff of the same hospitals. Also, 10 of the 16 MRSA strains (62.5 per cent) isolated from veterinarians were classified as type II by staphylococcal cassette chromosome mec (SCC mec ) typing and ST5 by multilocus sequence typing. Pulsed‐field gel electrophoresis analysis demonstrated that these 10 MRSA strains of SCC mec type II and ST5 were genetically identical or very similar to 9 MRSA strains isolated from infected horses hospitalised at these hospitals between 2009 and 2013. These results indicate that SCC mec type II and ST5 MRSA strains were probably transmitted between veterinarians and infected horses.